Factors Associated With Perceived Job Preparedness Among RNs: Results From a National Survey. (May 2020) - Zahnd, Whitney E.; Crouch, Elizabeth L.; Probst, Janice C.; Hunt McKinney, Selina; Abshire, Demetrius A.; Eberth, Jan M.
Abstract : This article examines perceived job preparedness by demographic and professional characteristics among practicing RNs who completed a national survey. Rural and male nurses felt less prepared for nursing practice and may benefit from tailored educational experiences to improve perceptions of being prepared for the workforce. Abstract : Supplemental digital content is available in the text.